Assessment of narghile (shisha, hookah) smokers’ actual exposure to toxic chemicals requires further sound studies (Libyan Journal of Medicine, 2011)
Tobacco smoking is hazardous for health. However, not all forms of tobacco use entail the same risks and the latter should be studied and compared in a sound realistic way. Smoking machines for cigarettes (which are consumed in a few minutes) were early designed as a tool to evaluate the actual intake of toxic substances (‘toxicants’) by smokers. However, the yields (tar, nicotine, CO, etc.) provided by such machines poorly reflect the actual human smoking behaviour known to depend on numerous factors (anxiety, emotions, anthropological situation, etc.). In the case of narghile smoking, the problems are even more complex, particularly because of the much longer duration of a session. A recent study from the US-American University of Beirut was based on a field smoking topography and claimed consistency with a laboratory smoking machine. We offer a point by point critical analysis of such methods on which most of the ‘waterpipe’ antismoking literature since 2002 is based.